1997
DOI: 10.1093/jmp/22.5.423
|View full text |Cite
|
Sign up to set email alerts
|

Embryo Research and Public Policy: A Philosopher's Appraisal

Abstract: The development of public policy on bioethical issues can be approached through substantive moral and philosophic reasoning, or through balancing perceived societal views as to what is ethically acceptable. The Human Embryo Research Panel had to apply the first approach to the question of the moral status of the preimplantation embryo. Only after concluding that the preimplantation embryo was not a full human subject could the panel consider the conditions under which embryo research was ethically acceptable, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…b Ustawy o embrionach). 23 Należy jednocześnie zwrócić uwagę na to, że dla porządków prawnych państw, w których dopuszczalne jest prowadzenie badań z wykorzystaniem ludzkich embrionów, charakterystyczne jest wprowadzenie nadzoru państwowego nad tymi badaniami, prowadzonego przez specjalnie powołane do tego celu organy oraz wymogu uzyskania zgody dawców materiału biologicznego (np. gamet) na określony sposób jego wykorzystania 24 .…”
Section: Przegląd Regulacji Dotyczących Dopuszczalności I Warunków Prowadzenia Badań Nad Ludzkimi Embrionalnymi Komórkami Macierzystymi Iunclassified
See 1 more Smart Citation
“…b Ustawy o embrionach). 23 Należy jednocześnie zwrócić uwagę na to, że dla porządków prawnych państw, w których dopuszczalne jest prowadzenie badań z wykorzystaniem ludzkich embrionów, charakterystyczne jest wprowadzenie nadzoru państwowego nad tymi badaniami, prowadzonego przez specjalnie powołane do tego celu organy oraz wymogu uzyskania zgody dawców materiału biologicznego (np. gamet) na określony sposób jego wykorzystania 24 .…”
Section: Przegląd Regulacji Dotyczących Dopuszczalności I Warunków Prowadzenia Badań Nad Ludzkimi Embrionalnymi Komórkami Macierzystymi Iunclassified
“…2 Stamzellengesetz) 26 . Prace z komórkami można prowadzić w celu osiągnięcia ważnych 23 Jest to podejście o tyle ciekawe, że różnicuje sytuację prawną w zasadzie takich samych bytów w zależności od celu, w jakim powstały i tego, czy ten cel został osiągnięty. 24 Isasi, Knoppers, op.…”
Section: Przegląd Regulacji Dotyczących Dopuszczalności I Warunków Prowadzenia Badań Nad Ludzkimi Embrionalnymi Komórkami Macierzystymi Iunclassified
“…History II: The hESC Controversy and the War on the ''Culture of Death'' In 1993, the U.S. National Institutes of Health (NIH) formed the Human Embryo Research Panel (HERP), which set forth guidelines delineating appropriate and inappropriate areas of embryo research (Tauer, 1997). In its report, the panel made a controversial recommendation, subsequently rejected by President Clinton, to permit federal funding for the creation of embryos for certain research purposes.…”
Section: History I: the Fetus Battlementioning
confidence: 99%
“…28 The NIH Human Embryo Research Panel expressed the idea that the preimplantation embryo is not a full human subject and does not merit full protection, either morally or legally, but it warrants serious moral consideration. 29 This panel suggested that some research neither directly therapeutic to the embryos themselves nor actually destructive to those embryos could be morally acceptable because embryos do not merit full protection. 30 Accordingly, in the context of using embryos in scientific research, "to protect embryos" can be interpreted as the importance of research goals and the handling method rather than the question of whether they may be destroyed.…”
Section: To Protect Embryos Versus To Respect Embryosmentioning
confidence: 99%